Dead zero : a Bob Lee Swagger novel - Hunter, Stephen (Bob Lee Swagger novel, 2010)
Marine Corps master sniper Bob Lee Swagger travels to the remote deserts and caves of Afghanistan to track down a renegade Marine who is using extreme measures to complete a mission